Effect of Home Visiting with Pregnant Teens on Maternal Health. Issue 3 (May 2016) - Samankasikorn, Wilaiporn; Pierce, Brittany; St. Ivany, Amanda; Gwon, Seok Hyun; Schminkey, Donna; Bullock, Linda
Abstract: Purpose: Determine the extent that participation in Resource Mothers Program (RMP) home visiting improves maternal health at 3 months postpartum. Study Design and Methods: A randomized controlled trial using RMPs in two urban and one rural location in a mid-Atlantic state. Community health workers from these RMPs enrolled teens into the study and the research team assigned participants to either the intervention group or telephone support control group using computerized randomization assignments. Data collection from baseline and 3 months postpartum using the Edinburgh Postnatal Depression Scale (EPDS) and the Prenatal Psychosocial Profile (PPP) is reported. Results: The sample included 150 pregnant teens with a mean age of 17 years. Mean self-esteem scores between groups were not significantly different at baseline, but the RMP group self-esteem scores improved significantly at the 3 months postpartum interview (36.40 ± 5.63 for RMP vs. 34.10 ± 4.29 telephone control group, p = 0.049). Neither group was at risk for depression at baseline or 3 months postpartum. Because 60% of the total sample identified as Hispanic, post hoc analysis revealed significantly different baseline stress mean scores between Hispanic and non-Hispanic teens ( p = 0.038); however, these differences were no longer significant by 3 months postpartum (p = 0.073). The EPDS scores by ethnicity were not different at baseline ( p = 0.875) but were significantly different at 3 months ( p = 0.007). Clinical Implications: The RMP home-visiting intervention can lead to improved self-esteem scores in teens, particularly in Hispanic teens. Improved self-esteem has been shown to lead to better parenting. Abstract : Home visiting may be an effective method of promoting health during pregnancy and postpartum. This randomized trial demonstrates positive outcomes for pregnant teens participating in a home visiting program.